Treatment changes following aberrant urine drug test results for patients prescribed chronic opioid therapy - Morasco, PhD, Benjamin J.; Krebs, MD, MPH, Erin E.; Cavanagh, MS, Renee; Hyde, MA, Stephanie; Crain, MSW, Aysha; Dobscha, MD, Steven K. (Journal of Opioid Management, 2015)
Background/objective: Urine drug testing (UDT) may be used to help screen for prescription opioid misuse. There are little data available describing usual pain care practices for patients who have aberrant UDT results. The goal of this research was to evaluate the clinical care for patients prescribed chronic opioid therapy (COT) and have an aberrant UDT. Design: Retrospective cohort study. Setting: VA Medical Center in the Pacific Northwest. Participants: Patients with chronic pain who were prescribed COT and had a UDT result that was positive for an illicit or nonprescribed substance. Main outcome measures: This was an exploratory study designed to document usual care practices. Results: Participants’ (n = 83) mean age was 49.5 (SD = 9.6) and 81.5 percent were male. The most common substances detected on UDT were marijuana (69 percent) or a nonprescribed opioid (25 percent); 18 percent had a UDT positive for two or more substances. Plans to modify treatment were documented in 69 percent of cases. The most common treatment change after aberrant UDT results was instituting more frequent UDTs, which occurred in 43 percent of cases. Clinicians documented plans to alter their opioid prescribing (eg, terminating opioids, requiring more frequent fills, changing opioid dose, or transitioning to another opioid) in 52 percent of cases, but implemented these changes in only 24 percent. Discussion: Current methods for optimizing treatment after obtaining aberrant UDT results should be enhanced. To improve the utility of UDT to reduce prescription opioid misuse, additional interventions and support for clinicians need to be developed and tested.